DEVELOPING ENGLISH SPEAKING THROUGH OME TV - Yusuf, Emi Marlina M; Talib, Ahmad; Tahir, Muh. (JTechLP: Journal of Technology in Language Pedagogy, 2024)
The objective of this research was to find out this study to determine whether using Ome TV could develop students' speaking skills. This research adapted a pre-experimental design. This research took place at SMAN 3 Makassar. The population of this research was the eleventh-grade students of SMAN 3 Makassar in the academic year 2022-2023. The XI IPA 2 class was selected to be the sample of this research. The research utilized a speaking test administered both as a pretest and a posttest. The results indicated that using Ome TV to develop English-speaking skills was effective. This is evidenced by the mean score of 7.49 on the pretest and 10.9 on the posttest, showing an increase of 45.4% in students' scores.